An Assessment Of Instructional Module In Basic And Higher Educational Institutions In Zambales: Plagiarism Issues - Froilan D Mobo; Abdul Rahmat (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
During the full Implementation of flexible learning in both basic and higher education, the majority of the schools opted to choose to use a modular approach rather than online learning. There are a lot of struggles encountered by both teachers and students. Part of the Struggle is the development of modular instructional materials. There are teachers that accidentally didn’t cite credible sources which reflected in their modules. Book Authors also suffered from copywriting and plagiarism issues because there are teachers that don’t know how to cite or give credit to the authors of the book or in some published research. This study will help both teachers and administrators of both basic and higher education on how to formalize a standard method on how to cite credible sources just like in a refereed research journal.